The social construction of the invisible mother: reflections from Pierre Bourdieu’s perspective - Cananéa, Lílian Viana Teixeira; Alves, Edvaldo Carvalho; Santos, Ana Cláudia de Araújo; Paiva, Mônica (Ciência da Informação em Revista, 2024)
This article approaches the image of the woman-mother and its social construction from the perspective of Pierre Bourdieu, aims to reflect on the female identity in the 21st century, especially of women-mothers, as well as to identify and discuss the logics that govern the perpetuation of gender culture in our society. As a result, the article lists these social actions as driving and reproducing agents of male domination, which results in a literature review, which incorporates the identity of the woman-mother and her resignification in the face of patriarchy, with emphasis on the role of the woman-mother. mother in the field of Information Science. The study is descriptive, exploratory and qualifying, while describing, registering, analyzing and interpreting facts or phenomena of reality, without any interference. In the case of exploratory research, its purpose is to favor a generic view of certain research questions, in general, themes that are little explored. Finally, qualitative research favors particularities and individual and group experiences, given that its target is to apprehend the behavior of a given social group. In this case, the inferences confirm the legitimization of elements that reproduce male domination in the face of the image of the woman-mother and her social role.